Mapping GLAMs: creating a national dataset of GLAMs to develop a categorical climate-change risk assessment scale - Edward Benoit, III; Jill Trepanier; Jennifer Vanos; Emily Fisher; Kaitlyn Bailey; Annie Waddell; Haley Moore; Mandy Hatman; Mary Sidwell; Symonne Russell; Virginia Seger; Paige Boutte; et al. (Information Research: An International Electronic Journal)
Introduction. The PROTECCT-GLAM project aims to assess and address climate risks for U.S. galleries, libraries, archives, and museums (GLAMs). The project team began with creating a national dataset of GLAMs.